Corticosterone differences rather than social housing predict performance of T-maze alternation in male CD-1 mice - Fitchett, Ann E.; Barnard, Christopher J.; Cassaday, Helen J. (Universities Federation for Animal Welfare, 2009)
This study examined the effects of social housing manipulations on body weight, corticosterone levels, and performance of T-maze alternation in male CD-1 mice. Males that adopted a dominant social rank were heavier than those that adopted a subordinate social rank. Dominant males also had lower corticosterone concentrations than the subordinates. However, there was little to suggest that these physiological indicators of social rank were moderated by housing condition. Indeed, statistical analysis confirmed that the difference in body weights was evident before males were socially housed. The mice showed high levels of spatial alternation on the T-maze from the start of testing so performance accuracy was high. Neither social rank nor housing condition had any clear categorical effect on T-maze performance. However, performance did fluctuate over successive blocks of testing and there was a negative association between accuracy on the T-maze and corticosterone levels (consistent with performance impairment because of elevated corticosterone). Therefore, under present conditions, individual differences in corticosterone were a better predictor of T-maze performance than were social rank or housing condition. The results of the present study lend further support to the proposition that corticosterone levels measured non-invasively in urine may be used to predict diverse welfare outcomes for laboratory mice, from body weight to cognitive performance. Moreover, intrinsic physiological parameters rather than external influences such as social housing may have more influence on mouse behaviour.